Práticas políticas e imaginário: a atuação do Morgado de Mateus nos “interminaveis” e “odiozos” conflitos verificados entre São Paulo e Minas Gerais (1765-1774) - Silva, Rafaela Ferreira da (2020)
The present thesis studies the performance of D. Luis Antonio de Souza Botelho Mourão, captain-general and governor of São Paulo, in the “endless” and “odiozos” conflicts verified between São Paulo and Minas Gerais between 1765 and 1774. The time frame of this research begins in 1765, when the 4th Morgado de Mateus (1722-1798) sent soldiers to the Rio Pardo mines (located in an area disputed by Minas Gerais and São Paulo) and extends to 1774, year in which the referred militar produced his last missive about the question of the division between S. Paulo and Minas Gerais. During this period, D. Luis Antonio idealized and promoted a series of initiatives that aimed to guarantee the possession of areas located in the western region of the Sapucaí River and obtain the “restitution” of a wide region located in the south of Rio Grande, currently known as South of the State of Minas Gerais - regions that the 4th Morgado de Mateus believed to have opulent mines that by the right of conquest belonged to paulistas. Having as scenario the disputes verified between residents and authorities of Minas Gerais and São Paulo for the possession of lands located in the western region of the Sapucaí River and the revival of discussions about the Roby Demarcation and geographic accidents that had already served to mark the limits between villages in São Paulo and Minas Gerais, we analyzed Dom Luis' performance in the Minas Gerais issue, seeking to reflect about political practices supported by this nobleman in these disputes, as well as aspects of the eighteenth century imaginary. The main sources used in this research were documents produced by Dom Luis such as: orders, maps, instructions, terms, and mainly letters sent to residents and to various authorities in Brazil and the Kingdom of Portugal about the Question of Minas Gerais. We have therefore compared these items with different documents produced by authorities and residents of the State of Brazil and the Kingdom of Portugal (to address the Question of Minas Gerais) over the decades before Dom Luis arrived in Portuguese America. These are, above all, requirements of the city councilors of São Paulo, representations of residents of the City of São Paulo, permits, royal orders, and finally, missives exchanged between civil and ecclesiastical authorities of the Kingdom of Portugal and Brazil involved in the said issue. We point that between 1765 and 1774, in the Question of Minas Gerais, Dom Luis (considered by some researchers as “authoritarian”, a “Pombaline governor” and an administrator guided by the voluntarist conception) made great efforts to promote gold exploration in areas considered part of the São Paulo Captaincy – against a important orientation of Pombal and demonstrating the strength of the expectation to find in the disputed region, “treasures” similar to those found in the central region of Minas Gerais. Significantly, in order to obtain the possession of these regions, Dom Luis fought the black legends of the paulistas and promoted many initiatives that are integrated with the corporatist logic, also reproducing ideas that for decades were part of the political repertoire used by paulistas in the disputes with Minas Gerais